2018
DOI: 10.1016/j.kint.2017.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Potassium intake modulates the thiazide-sensitive sodium-chloride cotransporter (NCC) activity via the Kir4.1 potassium channel

Abstract: Kir4.1 in the distal convoluted tubule plays a key role in sensing plasma potassium and in modulating the thiazide-sensitive sodium-chloride cotransporter (NCC). Here we tested whether dietary potassium intake modulates Kir4.1 and whether this is essential for mediating the effect of potassium diet on NCC. High potassium intake inhibited the basolateral 40 pS potassium channel (a Kir4.1/5.1 heterotetramer) in the distal convoluted tubule, decreased basolateral potassium conductance, and depolarized the distal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
145
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(151 citation statements)
references
References 43 publications
6
145
0
Order By: Relevance
“…The [K] o affected the activity of WNK4/SPAK/NCC signaling and its downstream targets in this model cell line as determined by measuring the levels of pWNK4, pSPAK, and pNCC level, respectively. The inverse effect of increasing [K + ] o on pWNK4 levels in cells expressing wild-type WNK4 was abolished by K channel blockers (tertiapin and Ba 2+ ), thus confirming that DCT K channels (such as KCNJ10) are the route for K entry into these cells, which facilitates the subsequent effects on the WNK4/SPAK/NCC pathway as observed in in vivo studies (Wang et al, 2018). The absence of a similar K + sensitivity to the phosphorylation states of the same proteins in cells expressing the Cl − insensitive mutants, WNK4 LLFF and WNK4 LF KD respectively, emphasises the importance of the WNK4 Cl − binding and kinase domains for transducing the membrane potential changes caused by altered [K + ] o .…”
Section: Discussionsupporting
confidence: 65%
“…The [K] o affected the activity of WNK4/SPAK/NCC signaling and its downstream targets in this model cell line as determined by measuring the levels of pWNK4, pSPAK, and pNCC level, respectively. The inverse effect of increasing [K + ] o on pWNK4 levels in cells expressing wild-type WNK4 was abolished by K channel blockers (tertiapin and Ba 2+ ), thus confirming that DCT K channels (such as KCNJ10) are the route for K entry into these cells, which facilitates the subsequent effects on the WNK4/SPAK/NCC pathway as observed in in vivo studies (Wang et al, 2018). The absence of a similar K + sensitivity to the phosphorylation states of the same proteins in cells expressing the Cl − insensitive mutants, WNK4 LLFF and WNK4 LF KD respectively, emphasises the importance of the WNK4 Cl − binding and kinase domains for transducing the membrane potential changes caused by altered [K + ] o .…”
Section: Discussionsupporting
confidence: 65%
“…The Effect of LS or HS Intake on NCC Is Compromised in Ks-Kir4.1 KO Mice Previous studies have demonstrated that a hyperpolarization in the DCT is associated with an increase in NCC activity, whereas a depolarization of the DCT is associated with a decrease in NCC activity. [14][15][16] After demonstrating that the deletion of Kir4.1 abolished the effect of dietary Na + intake on the basolateral K + conductance and DCTmembrane potential, we suspect that the effect of dietary Na + intake on NCC should be absent or attenuated in Ks-Kir4.1 KO mice. Thus, we next examined the effect of dietary Na + intake on NCC in WT and Ks-Kir4.1 KO mice on LS, NS, and HS diets for 7 days (four male and three female mice for each group).…”
Section: Resultsmentioning
confidence: 99%
“…15 A large body of evidence has convincingly demonstrated that dietary Na + and K + intake play an important role in the regulation of NCC activity: low potassium or low sodium (LS) intake stimulates whereas high potassium or high sodium (HS) intake inhibits NCC activity. [14][15][16][20][21][22][23] Furthermore, our previous experiments have demonstrated that Kir4.1 plays a key role in mediating the effect of dietary K + intake on NCC because the deletion of Kir4.1 completely abolished the effect of dietary K + intake on NCC. 16 Thus, it raises the possibility whether Kir4.1 in the DCT is also involved in mediating the effect of dietary Na + intake on the thiazide-sensitive NCC.…”
mentioning
confidence: 91%
See 2 more Smart Citations